Fuel Ethanol Production from Eucalyptus Globulus Wood by Autocatalized Organosolv Pretreatment Ethanol-Water and Ssf - Yanez-Sanchez, M (John Wiley and Sons Ltd, 2013)
BACKGROUND: Lignocellulosic biomass (LCB) offers the only sustainable alternative to the use of fossil fuels as oil by employing its main components (cellulose, hemicellulose and lignin) as a carbon source for the production of biofuels, energy and value-added chemicals. The aim of the present study was to investigate ethanol production from organosolv pretreated Eucalyptus globulus wood, carrying out the simultaneous sacharification and fermentation (SSF) process at a substrate loading of 10 and 15% (w/v) and using concentrations of 6 and 12 g L-1 of the thermally acclimatized S. cerevisiae IR2T9-a strain. These SSF experiments were also evaluated by increasing the enzyme loading in the reaction medium. Finally, a comparison was made between separate hydrolysis and fermentation (SHF) and SSF processes. With the information obtained and from published information, a general mass balance was developed. RESULTS: The highest ethanol concentration (?42 g L-1) in the fermentation broth was obtained at a substrate consistency of 15% (w/v), enzyme loading of 20 FPU cellulase 40 UI ?-glucosidase g-1 of pretreated material and using both S. cerevisiae strain IR2-9a concentrations (6 and 12 g L-1). CONCLUSION: The results of enzymatic hydrolysis (EH) show that increasing substrate content from 10 to 15% (w/v) decreases the conversion efficiency of cellulose to glucose. Furthermore, the mass balances of the process indicate that the SSF process is a better alternative than the SHF configuration, because larger amounts of ethanol can be obtained. © 2012 Society of Chemical Industry.